Early Transpyloric Tube Feeding in Preventing Adverse Respiratory Events in Extremely Low Birth Weight Infants - Shinya Tanaka; Fumihiko Namba; Ken Nagaya; Naohiro Yonemoto; Shinya Hirano; Itaru Yanagihara; Hiroyuki Kitajima; Masanori Fujimura (Biomedicines)
Background: It has been demonstrated that aspiration during endotracheal intubation in preterm infants with gastroesophageal reflux is a contributing factor in the worsening of lung diseases and the development of bronchopulmonary dysplasia (BPD). This study aims to compare the safety and efficacy of early transpyloric (TP) tube feeding with that of nasogastric (NG) tube feeding in relation to BPD. Methods: The study population consisted of 39 extremely low birth weight infants (ELBWIs) with mechanical ventilation and an enteral feeding volume of 50 mL/kg/day, which were randomly assigned to different groups based on the method of tube feeding. The primary outcome was the incidence of adverse events. Results: The hazard ratio for primary adverse events was significantly lower in the TP group. The TP group had a median time of 34 days (range 24–85) and the NG group 24 days (range 13–70). In general, neither group exhibited severe intestinal complications or poor growth. Conclusions: Early TP tube feeding may be a safer alternative method of NG tube feeding for intubated ELBWIs and has been shown to reduce the frequency of adverse respiratory events.